The Influence of Non-State Actors in Climate Policymaking - Michael, Evans (Journal of Climate Policy, 2023)
Purpose: The main objective of this study is to explore the influence of non-state actors in climate policymaking. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the influence of non-state actors in climate policymaking. Preliminary empirical review revealed that non-state actors, including civil society organizations, corporations, cities, and transnational networks, exert considerable influence through various mechanisms such as advocacy, mobilization, technical expertise, and collaboration with governments. Their involvement is driven by diverse motivations, including environmental stewardship, economic interests, and the pursuit of social and ethical values. One key takeaway from this study is that non-state actors are not merely peripheral actors in the climate policy landscape; rather, they are central to the process of crafting effective climate policies. Their contributions span from raising public awareness and holding governments accountable to providing innovative solutions and pushing for ambitious climate targets. However, the extent of their influence can vary significantly depending on the specific context, the level of government involved, and the particular issue at hand. Unique Contribution to Theory, Practice and Policy: The Network Governance theory, Interest Group theory and the Policy Diffusion theory maybe used to anchor future studies on climate policymaking. Recommendations made from the study include the following: enhancing transparency and accountability, strengthening collaboration, promoting inclusivity, supporting capacity building and global knowledge sharing.